Pengaruh Penggunaan Silase Limbah Sawi Putih (Brassica pekinensia L.) terhadap Konsumsi dan Kecernaan Energi dan Protein pada Ternak Babi Grower - Jems Ndolu, Dedi; Sembiring, Sabarta; Suryani, Ni Nengah; Aryanta, I Made S. (Yayasan Sumber Daya Manusia Cerdas, 2024)
The aim of this research was to determine the effect of using chicory waste silage (Brassica pekinensis L) in rations on energy and protein consumption and digestibility in grower pigs. The livestock used were 12 grower phase landrace crossbreed pigs aged 3-4 months with initial body weights ranging from 29-52 kg and an average of 36 kg (CV = 17.72%). This research used an experimental method with a Randomized Block Design (RBD) consisting of four treatments and three replications so that there were 12 experimental units. The treatments used were R0: 100% basal ration, R1: 90% basal ration + 10% chicory waste silage, R2: 85% basal ration + 15% chicory waste silage and R3: 80% basal ration + 20% chicory waste silage. The variables studied were ration consumption, energy consumption, protein consumption, energy digestibility and protein digestibility. The results showed that the treatment had no significant effect (P>0.05) on all variables. Based on the results of this research, it can be concluded that the use of chicory waste silage (Brassica pekinensis L) in rations at levels of 10%, 15% and 20% has the same effect on energy and protein consumption and digestibility